Effect of Engineered Nickel Oxide Nanoparticle on Reactive Oxygen Species–Nitric Oxide Interplay in the Roots of Allium cepa L. - Manna, Indrani; Sahoo, Saikat; Bandyopadhyay, Maumita (Frontiers in Plant Science, 2021)
Scientists anxiously follow instances of heavy metals augmenting in the environment and undergoing bioaccumulation and trace their biomagnification across food webs, wary of their potent toxicity on biological entities. Engineered nanoparticles supplement natural pools of respective heavy metals and can mimic their effects, exerting toxicity at higher concentrations. Thus, a thorough understanding of the underlying mechanism of this precarious interaction is mandatory. Most urban and industrial environments contain considerable quantities of nickel oxide nanoparticles. These in excess can cause considerable damage to plant metabolism through a significant increase in cellular reactive oxygen species and perturbation of its cross-talk with the reactive nitrogen species. In the present work, the authors have demonstrated how the intrusion of nickel oxide nanoparticles (NiO-NP) affected the exposed roots of Allium cepa: starting with disruption of cell membranes, before being interiorized within cell organelles, effectively disrupting cellular homeostasis and survival. A major shift in the reactive oxygen species (ROS) and nitric oxide (NO) equanimity was also observed, unleashing major altercations in several crucial biochemical profiles. Altered antioxidant contents and upregulation of stress-responsive genes, namely, Catalase, Ascorbate peroxidase, Superoxide dismutase, and Rubisco activase, showing on average 50–250% rise across NiO-NP concentrations tested, also entailed increased cellular hydrogen peroxide contents, with tandem rise in cellular NO. Increased NO content was evinced from altered concentrations of nitric oxide synthase and nitrate reductase, along with NADPH oxidase, when compared with the negative control. Though initially showing a dose-dependent concomitant rise, a significant decrease of NO was observed at higher concentrations of NiO-NP, while cellular ROS continued to increase. Modified K/Na ratios, with increased proline concentrations and GABA contents, all hallmarks of cellular stress, correlated with ROS–NO perturbations. Detailed studies showed that NiO-NP concentration had a significant role in inducing toxicity, perturbing the fine balance of ROS–NO, which turned lethal for the cell at higher dosages of the ENP precipitating in the accumulation of stress markers and an inevitable shutdown of cellular mechanisms.